2016
DOI: 10.1007/s10518-016-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of alternative intensity measures for the seismic assessment of monolithic free-standing columns

Abstract: This paper deals with the dynamic response of a free-standing ancient column in the Roman Agora of Thessaloniki, Greece as a means to shed more light on the complex behaviour of rocking bodies under seismic excitation. Numerical analyses utilizing discrete element method were carried out with the use of multiple seismic records selected based on the disaggregation of the seismic hazard for the region of interest. To identify their impact on structural performance, earthquake Intensity Measures, such as Peak Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
(43 reference statements)
3
31
0
1
Order By: Relevance
“…These conclusions are in agreement with the deterministic rocking response to a sinusoidal pulse; a small block overturns as soon as it commences rocking, and hence, overturning is dominated by the peak ground acceleration. Further, corroboration to these findings came from the recent studies of Kavvadias et al and Pappas et al who indicated that velocity‐based, as well as frequency‐based, IMs exhibit strong correlation with the seismic response of freestanding rocking columns (with R >2 m).…”
Section: Introductionsupporting
confidence: 61%
“…These conclusions are in agreement with the deterministic rocking response to a sinusoidal pulse; a small block overturns as soon as it commences rocking, and hence, overturning is dominated by the peak ground acceleration. Further, corroboration to these findings came from the recent studies of Kavvadias et al and Pappas et al who indicated that velocity‐based, as well as frequency‐based, IMs exhibit strong correlation with the seismic response of freestanding rocking columns (with R >2 m).…”
Section: Introductionsupporting
confidence: 61%
“…They concluded that the blocks with imperfections are less stable than the theoretically perfect ones. Pappas et al [60] numerically explored the behavior of an ancient cylindrical column with a height of 6 m and a diameter of 0.66 m with the intension of defining proper ground motion intensity measures to characterize the rocking response of such structures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, a design method that uses a size‐independent rocking spectrum is suggested. This should be taken into account when intensity measures for rocking structures designed not to get close to overturning are explored.…”
Section: Discussionmentioning
confidence: 99%